Addition of tea tree oil (Melaleuca alternifolia) in diet minimize biochemical disturbances in silver catfish Rhamdia quelen exposed to the antiparasitic amitraz - dos Reis T.R.* (2021)
© 2021 Elsevier B.V.In the present study, we evaluated diets supplemented with Melaleuca alternifolia essential oil (tea tree oil - TTO) as a growth promoter and its possible hepatoprotective effects in Rhamdia quelen exposed to the insecticide amitraz. Six groups (8 per group, in triplicate) were tested: control A (basal diet), B (basal diet + TTO 1.0 mL/kg), C (basal diet +0.84 mL/kg amitraz), D (basal diet +1.19 mL/kg amitraz), E (basal diet +1.0 mL/kg TTO + 0.84 mL/kg amitraz) and F (basal diet + TTO 1.0 mL/kg + 1.19 mL/kg amitraz). Initially R. quelen received diets according to each group. After 14 days, four groups were exposed to two levels of amitraz for a period of 7 days, and were later transferred to amitraz-free water for recovery. We measured levels of reactive oxygen species (ROS) and lipoperoxidation (LOOH) in liver tissue, and activities of enzymes involved in energy metabolism, adenylate kinase (AK) and pyruvate kinase (PK), in addition to zootechnical indices such as length, weight body and fish weight gain. ROS and LOOH levels increased significantly (p < 0.05) in fish exposed to amitraz concentrations, especially in groups of fish not supplemented with TTO. By contrast, AK and PK enzyme activities were significantly lower (p < 0.05) for the groups exposed to amitraz compared to the unexposed group. Finally, fish supplemented with TTO showed better (p < 0.05) zootechnical performance. Addition of TTO minimizes biochemical disturbances in fish exposed to amitraz and serves as a natural additive to improve fish production.